A high-performance protein preparation approach in a single column-free step - Huang, Yuan; Zhang, Yuanyuan; Yang, Xiaofeng; Lin, Zhanglin (Trends in biotechnology (Regular ed.), 2025)
The cleavable self-aggregating tag 2.0 (cSAT2.0) incorporates the propeptide (PEP) of subtilisin from Deinococcus gobiensis, enabling protein purification with over 98% purity in a single, column-free step.Purified protein yields ranged from 24 mg/l to 89 mg/l for one model peptide and five model proteins in shake-flask experiments.A yield of 1.4 g/l of purified caplacizumab with over 99% purity was achieved in a 5-l fermenter.The cSAT2.0 method efficiently produces the model peptide and proteins in a high-throughput 96-well plate format. Protein purification remains a formidable and costly technical obstacle in biotechnology. Here, we present a new column-free method, utilizing the cleavable self-aggregating tag 2.0 (cSAT2.0) scheme, to streamline protein production in Escherichia coli, yielding high quantities with exceptional purity. In shake-flask experiments using lysogeny broth (LB) medium, the cSAT2.0 scheme successfully produced one peptide and five proteins, with yields ranging from 24 mg/l to 89 mg/l, and purity levels exceeding 98%. The cSAT2.0 scheme also enabled high-throughput protein preparation on microplates. Furthermore, we scaled up the fermentation process for caplacizumab, achieving 1.4 g/l of highly purified protein in a 5-l fermenter. Our results demonstrate that the cSAT2.0 scheme can serve as an economical and robust platform for protein production from microplate to fermenter scales. [Display omitted] We present the cleavable self-aggregating tag 2.0 (cSAT2.0) scheme, a single-step, column-free scheme for protein purification in Escherichia coli, achieving over 98% purity across a range of peptides and proteins. This versatile approach is scalable from microplates to fermenters, offering significant potential for applications in biological and pharmaceutical research and industry. The cleavable self-aggregating tag 2.0 (cSAT2.0) system has been validated across a diverse set of targets, including one peptide and five proteins (one therapeutic protein, two nanobodies, and two enzymes), primarily at the laboratory scale. When applied to caplacizumab production in a 5-l fermenter, it yielded an impressive 1.4 g/l with a purity >99%. More recently, we obtained preliminary data demonstrating the production of human growth hormone (hGH) at 2.5 g/l and >98% purity in a 5-l fermenter. These results underscore the effectiveness and robustness of this method for potential industrial applications. Based on this progress, we propose that the cSAT2.0 system has reached NASA’s Technology Readiness Level (TRL) 6, indicating its readiness for real-world implementation.